Bairro Pedra 90 e suas configurações territoriais : o caso dos moradores da terceira idade - Iten, Etson (2018)
This work aims to contribute to the promotion of new public policies for the benefit of third-age residents of Pedra 90. The accelerated growth in the world of contemporary cities is inherent in the development of capitalist production. In this sense it is perceived the fragmentation of the space in its different territorialities, and the socio-spatial segregation. The research seeks to explain the socio-spatial dynamics of the neighborhood Pedra 90 from its formation to the present day, with the object of studies being the elderly who have been investigated their socio-spatial relationship in cultural, economic and political aspects. For this we searched for bibliographical studies of Geography thinking and its concepts of the dynamics and production of space in urban areas. In the area of studies, fieldwork was carried out with visits to the homes of the elderly, with the application of questionnaires, interviews, photographs and data collection of Pedra 90 neighborhood, which included the participation of other residents and local authorities. objective of this research. The analyzes show that space has been produced and reproduced by different interests, creating hierarchies and territorial powers, and the results are in the accelerated growth of the neighborhood and the slow development of the social function, which has been reinforcing sociospatial segregation interfering in the quality of life of the residents, these problems are confirmed in the last chapters of this work through interviews, photographs and transcribed accounts of residents and neighborhood authorities. According to residents, the problems of the neighborhood could be better resolved if there were more efficiency in the planning of public resources, which are often applied for other purposes rather than being applied in public areas.